EFFECT OF WORKING CAPITAL TO TOTAL ASSETS, DEBT TO EQUITY RATIO, TOTAL ASSET TURN OVER, AND RETURN ON ASSETS ON PROFIT GROWTH - Ira Yudi Farmawati; Ahmad Efan; Setyo Arief Arachman (Green Publisher, 2023)
This study aims to determine the effect of Working Capital to Total Assets, Debt to Equity Ratio, Total Asset Turnover, Return on Assets on Profit Growth. This type of research is descriptive quantitative research. The population of this research is a Manufacturing company in the Plastic and Packaging Sub-Sector for the 2015-2020 period. The sample was taken using a purposive sampling technique. The sample consisted of 10 companies from 14 companies. Multiple Linear Regression analysis method with IBM SPSS 25.0 analysis tool. From the results of data processing, it is concluded that Working Capital to Total Assets, Debt to Equity Ratio, Return On Assets have no significant effect on Profit Growth, while Total Asset Turnover has a significant effect on Profit Growth